2019
DOI: 10.13189/ujer.2019.070230
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Emotional Intelligence of Learners of Turkish as a Foreign Language on Reading Comprehension Skills and Reading Anxiety

Abstract: In the present study that measured the emotional intelligence of the students who were learning Turkish as a foreign language, the aim was to determine whether the emotional intelligence of the students affected their reading comprehension skills and reading anxiety. Thus, initially, the Schutte Emotional Intelligence Scale was adapted for foreign students after the required approvals were obtained. Then, the correlations between the emotional intelligence of the students and their reading anxiety and reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
7
1
1
Order By: Relevance
“…In a study conducted by Taşlıyan et al (2015) to demonstrate the correlations between emotional intelligence, communication skills and academic achievement levels of college students and to determine whether emotional intelligence, communication skills and academic achievement levels differed based on demographics, it was determined that there was a significant correlation between emotional intelligence and communication skills and academic achievements. Stottlemyer (2002), Fahim and Pishghadam, (2007), and Ateş (2019) reported a significant correlation between academic achievement and emotional intelligence. Karadüz (2010) investigated the listening strategies of pre-service Turkish language and classroom teachers and demonstrated that along with several affective factors, instructional approaches limited the listening skills of pre-service teachers.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 98%
See 2 more Smart Citations
“…In a study conducted by Taşlıyan et al (2015) to demonstrate the correlations between emotional intelligence, communication skills and academic achievement levels of college students and to determine whether emotional intelligence, communication skills and academic achievement levels differed based on demographics, it was determined that there was a significant correlation between emotional intelligence and communication skills and academic achievements. Stottlemyer (2002), Fahim and Pishghadam, (2007), and Ateş (2019) reported a significant correlation between academic achievement and emotional intelligence. Karadüz (2010) investigated the listening strategies of pre-service Turkish language and classroom teachers and demonstrated that along with several affective factors, instructional approaches limited the listening skills of pre-service teachers.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 98%
“…It was determined that the Emotional Evaluation Centered on Others scores of the females were higher when compared to that of the males. Ateş (2019) investigated the effect of emotional intelligence on reading comprehension and reading anxiety scores of those who were learning Turkish as a foreign language and determined that the total emotional intelligence scores of female students were higher than male students. There were no significant differences between student Self-Centered Emotional Evaluation, Self-Centered Emotional Regulation, Emotional Regulation Centered on Others, and Total Emotional Intelligence scores based on the gender variable.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian menunjukkan kecerdasan memberikan pengaruh 28,7% terhadap penyesuaian diri mahasiswa jurusan bimbingan dan konseling. Individu yang memiliki kecerdasan tinggi, mereka akan: mudah mencerna (Ates, 2019); merespons suasana hati secara tepat; mampu berkomunikasi secara tepat (Cherry dkk., 2013;Zhu dkk., 2016); memiliki empati yang baik (Abe dkk., 2018); mampu menyelesaikan persoalan-persoalan; menghormati dan menghargai pendapat orang lain; berinteraksi (Dewi dkk., 2016); serta mampu melihat segala sesuatu dari berbagai sudut pandang. Tentu kemampuan ini sangat dibutuhkan dalam proses penyesuaian diri, karena individu dituntut untuk mengatasi keteganganketegangan; frustasi; dan konflik yang dialaminya.…”
Section: Pembahasanunclassified
“…Though some studies to date have investigated EFL learners' emotional intelligence as well as their metacognitive strategies (Ateş, 2019;Ebrahimi, Khoshsima, Zare-Behtash & Heydarnejad, 2018;Hasanzadeh & Shahmohamadi, 2011;Hashemi & Ghanizadeh, 2011;Nelson & Low, 1999;Pishghadam, 2009;Ranjbar Mohammadi, Saeidi & Ahangari, 2020;Taheri & Hedayat Zade, 2018;Taheri, Sadighi, Bagheri & Bavali, 2019), the relationship between these two concepts still remains to be further probed. More specifically, in the Iranian EFL learning context, reading skill is of great significance since developing this skill has been one of the prime objectives of EFL learning in the Iranian L2 learning curriculum.…”
Section: Introductionmentioning
confidence: 99%